2020
DOI: 10.3390/en13092342
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Energy-Saving Operations System Using Robotic Process Automation

Abstract: We have developed an energy-saving operations system featuring remote operation of central monitoring equipment installed in a building. This system applies robotic process automation to remote operation to automatically perform energy-saving operations on behalf of the operations manager. Furthermore, as another feature, the system requires only a local area network to connect to the central monitoring equipment enabling automatic operation to be performed regardless of the specifications of the central monit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Finally, a similar approach to this research can be found in the work of Shah et al [105]. This work was a digital twin framework that was developed for temperature monitoring through sensors linked to Programmable Logic Controller (PLC) programs and open-source software.…”
Section: Robotic Process Automationmentioning
confidence: 92%
See 1 more Smart Citation
“…Finally, a similar approach to this research can be found in the work of Shah et al [105]. This work was a digital twin framework that was developed for temperature monitoring through sensors linked to Programmable Logic Controller (PLC) programs and open-source software.…”
Section: Robotic Process Automationmentioning
confidence: 92%
“…Regarding the application of RPA in civil engineering, sensors, and monitoring, three papers were found that were published between 2020 and 2021. Then, concerning the field of study shown in Figure 4, [103] was related to the integration between RPA and Artificial Intelligence (AI) and [104] and [105] were linked to civil engineering. These articles are summarised in Table 3.…”
Section: Robotic Process Automationmentioning
confidence: 99%
“…In the BPO and SSC sector, there has even been talk of cannibalizing the traditional method of conducting business [44] (p. 50). It should be emphasized that, currently, companies from other sectors, for example, utilities [45], use software robots.…”
Section: Rpa Implementation In the Context Of Organizational Changesmentioning
confidence: 99%
“…Using advanced software robots, RPA tools enable the automation of tasks thus far carried out by humans [6]. Today, the main users of these solutions include enterprises from the financial [7,8] and BPO/SSC [9][10][11] sectors in particular and, less often, those from the utilities sector [12,13]. Such enterprises are making the decision to implement RPA tools because they provide several benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Such enterprises are making the decision to implement RPA tools because they provide several benefits. The most important among them include reducing the costs of performing business processes; increasing the ability to carry out such processes without raising headcounts; improving employee experience by freeing employees from performing the most mundane and routine activities; improving the quality of the products/services delivered as a result of minimizing the number of errors committed by humans while performing business processes; and, finally, increasing the organizations' innovations by enabling the fast prototyping of new products/services that require various systems to be integrated, without the need to engage IT departments [6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%